Параметрическая идентификация S-системы с применением модифицированного алгоритма клонального отбора - Фефелов, А.А.; Литвиненко, В.И.; Таиф, М.А.; Лурье, И.А. (Управляющие системы и машины, 2017)
Предложен метод реконструкции генных регуляторных сетей, который в сочетании с алгоритмом оптимизации (эволюционным или иммунным) позволяет повысить скорость и точность решения задачи параметрической идентификации S-системы. Изложена суть метода последовательной трансформации пространства решений, управляемой результатами работы алгоритма оптимизации. Запропоновано метод реконструкції генних регуляторних мереж, який в поєднанні з алгоритмом оптимізації (еволюційним або імунним) дозволяє підвищити швидкість і точність розв’язання задачі параметричної ідентифікації S-системи. Викладено суть методу послідовної трансформації простору розв’язань, керованої результатами роботи алгоритму оптимізації. Purpose. The aim of this work is to create an effective method of the optimal parameters of the mathematical model of a gene regulatory network searching based on the ordinary differential equations system represented in the form of S-system. Method. A method is based on the successive transformation of decision space, guided by the results of the separate starting of clonal selection algorithm, hereupon space compresses in the vicinity of the global optimum. Results. A method for reconstructing the gene regulatory networks based on a modified clonal selection algorithm is developed. The method uses time series data of the gene expression profiles for searching interconnections between GRN components. The efficiency of the proposed method is confirmed by the experimental studies. Conclusion. The developed method and the algorithm increase the speed of the convergence of the optimization algorithms, and at the same time improve their accuracy in solving the problem of parametric identification of S-System. The proposed method can be used for modification of the evolutionary algorithms or artificial immune systems. Besides, in our future research we plan to test the method effectiveness on the real biological data.